The Influence Of Intellectual Capital And Institutional Ownership On Financial Performance With Corporate Social Responsibility As A Moderation Variable - Misdar Misdar (Publikasi Indonesia, 2023)
This study aims to determine and analyze the influence of intellectual capital and institutional ownership on financial performance withsocial responsibility as moderation. Population a inthis study is bank subsector companies listed on the Indonesia Stock Exchange in 2019-2021. The sampling method used is purposive sampling. The information used in this study was obtained from financial information published on www.idx.co.id website.